Open Repair of a 12-cm Posttraumatic Aneurysm of Right Subclavian Artery - Tigkiropoulos, Konstantinos; Chalvatzoulis, Omiros; Chalvatzoulis, Eleftherios; Stavridis, Kyriakos; Karamanos, Dimitrios; Lazaridis, Ioannis; Efstathiou, Andreas; Saratzis, Nikolaos (Frontiers in Surgery, 2017)
Purpose To present a rare case of a patient with a 12-cm posttraumatic right subclavian artery aneurysm successfully treated with aneurysmectomy and innominate-axillary bypass. Case report A 54-year-old man presented to the emergency department due to progressive dyspnea and hoarseness of voice. His medical record was unremarkable except that he had right-sided pneumothorax and multiple rib fractures from a car accident 16 years ago. A chest X-ray showed a mass in the upper lobe of the right lung, and the patient was hospitalized for further investigation. A computed tomography (CT) with intravenous contrast of the thorax was performed, which depicted a giant aneurysm of the right subclavian artery. Vascular and cardiothoracic surgeons were consulted immediately, and the operation was scheduled. Aneurysmectomy and innominate-axillary bypass were performed. The patient had an uncomplicated progress and was discharged on 5 days followed by a single antiplatelet therapy and symptom-free. Conclusion Posttraumatic subclavian artery aneurysm is a rare entity. Imaging of the thorax is essential for the diagnosis and surgical preparation of the patient. Open repair remains the gold standard therapy for subclavian artery aneurysm despite the improvements in endovascular surgery in such huge aneurysms.